2018
DOI: 10.1002/suco.201700226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementary cementitious materials on the resistance of cement paste to carbonic acid water

Abstract: Cement pastes blended with fly ash or slag suffering from carbonic acid water were investigated. Thermogravimetric analysis was performed to determine the effect of fly ash and slag on CH content in cement pastes. Mercury intrusion porosimetry was used to characterize the effect of fly ash and slag on pore structure of cement pastes. Decalcification shrinkage and corrosion depth were determined to characterize the deterioration of cement paste after corrosion. The results show that the decalcification shrinkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Furthermore, cement formulations with higher water-to-solids ratio, BP 0.25 (W/S = 0.439) and BP 0.50 (W/S = 0.438), have greater resistance to carbonation than samples with higher density: BP 1.00 (W/S = 0.436), BP 2.50 (W/S = 0.429) and BP 5.00 (W/S = 0.419). From these results, we found that cement formulations with low basalt powder content (≤ 0.50 wt.%) shows the best chemical resistance to CO 2 , confirming the literature statement that even small SCM additions can significantly alter the properties of the cement paste (Ghafari et al, 2016;Lothenbach et al, 2011;Paris et al, 2016;Yin et al, 2018). However, the literature argues that cement formulations with higher density are expected to have greater resistance to carbonation (Costa et al, 2019;Torsaeter et al, 2013).…”
Section: Chemical Resistance Of Cement Formulationssupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, cement formulations with higher water-to-solids ratio, BP 0.25 (W/S = 0.439) and BP 0.50 (W/S = 0.438), have greater resistance to carbonation than samples with higher density: BP 1.00 (W/S = 0.436), BP 2.50 (W/S = 0.429) and BP 5.00 (W/S = 0.419). From these results, we found that cement formulations with low basalt powder content (≤ 0.50 wt.%) shows the best chemical resistance to CO 2 , confirming the literature statement that even small SCM additions can significantly alter the properties of the cement paste (Ghafari et al, 2016;Lothenbach et al, 2011;Paris et al, 2016;Yin et al, 2018). However, the literature argues that cement formulations with higher density are expected to have greater resistance to carbonation (Costa et al, 2019;Torsaeter et al, 2013).…”
Section: Chemical Resistance Of Cement Formulationssupporting
confidence: 82%
“…After identifying the morphological and surface characteristics of the basalt powder, the mineral composition of the raw material was characterized by means of XRD (Table 2 and Figure S3). The mineral composition of SCM defines its reactivity during the hydration process, the role performed by the additive in the cement formulation, and indicates which are the mineral phases that will be generated after the curing process (Lothenbach et al, 2011;Paris et al, 2016;Yin et al, 2018).…”
Section: Basalt Powder Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 Although the effect of accelerated carbonation treatment on RCAs originating from blended concrete has not been sufficiently investigated, information on the carbonation resistance of blended cement systems as part of the durability properties is widely available. For example, it was reported by Morandeau et al 27 and Yin et al 28 that carbonating cement paste with increasing FA content resulted in increased carbonation depth, showing almost a linear relationship and a pore coarsening effect was observed. Meanwhile, GS-blended concrete was found to have a higher carbonation resistance than plain concrete because of the denser microstructure that was less permeable to CO 2.…”
Section: Introductionmentioning
confidence: 99%